STRATEGI MENINGKATKAN PENJUALAN DI ERA DIGITAL - Santy Permata Sari (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
As times change, consumption behavior is entering a new phase, especially in the technological era. It's hard to guess what products or services are in demand. Even consumption models or styles change, making things more difficult. Of course this impact, already felt. The number of closed shops, malls, supermarkets is evidence that the digital era provides a space for consumer democracy. Then there is only one way, namely marketing reform. This research was conducted to identify and analyze consumption behavior in the digital age, in order to increase sales. Of course, the immediate expected effect is to be able to make new marketing policies as a logic to thinking. A qualitative approach was chosen to describe the purchase behavior in real terms. By asking a few random questions to respondents about online retail purchases. Approximately 100 respondents were selected through certain criteria to see the symptoms. The results show that consumers in this era are ready with an online purchasing model. The basic reason is convenience. The convenience referred to relates to marketing attributes such as being able to be done anywhere, saving time and money, lower prices, flexible payment methods, and more friendly service